Utilization of Controlled Oven Drying Method to Produce Export Quality of Coffee Peel and Beans (Coffea arabica L.) - Siti Maimunah; Andre Prayoga; Dyna Grace Romatua Aruan; Roberto Roy Purba (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Karo regency as supplier of coffee, especially around Jaranguda village. Coffee is one of Indonesia's leading export commodities. A unique approach is required to enhance both the quantity and quality of coffee. Drying is a crucial step to ensure the peel and coffee beans maintain their quality after harvest. This study aims to determine whether drying using a drying oven has an effect on water content and nutritional information. Post-harvest processing methods included wet sorting, separation of peel and coffee beans, washing, drying, analysis of coffee peel characteristics, and analysis of nutrients in coffee beans. The analysis revealed that the water content of Arabica coffee beans was 1.11 %, while the analysis of nutrients and non-nutrients per 100 g of coffee beans revealed the following: total energy 417.34 kcal, fat energy 72.90 kcal, ash content 4.68 %, carbohydrates 72.17 %, total fat content 8.10 %, protein content 13.94 %, saturated fat 3.70 %, and sodium 6.53 mg. The analysis of coffee peel Simplicia revealed water content of 6.69 %, water-soluble extract content of 25.57 %, ethanol-soluble extract content of 13.79 %, ash content of 1.90 %, and acid-insoluble ash content of 1.43%. Analysis results of the characteristics of coffee peel meet the requirements of the Indonesian Herbal Pharmacopoeia Edition II in 2017. The food label includes nutritional value information, also known as nutrition facts, which details the nutritional content of the food ingredients. This information is crucial as it provides valuable insights and enhances the overall value of the product